Reliability optimization in stochastic domain via genetic algorithm. Issue 6 (27th May 2014) - Sahoo, Laxminarayan; Kumar Bhunia, Asoke; Roy, Dilip
Abstract : Purpose: – The purpose of this paper is to formulate the reliability optimization problem in stochastic and interval domain and also to solve the same under different stochastic set up. Design/methodology/approach: – Stochastic programming technique has been used to convert the chance constraints into deterministic form and the corresponding problem is transformed to mixed-integer constrained optimization problem with interval objective. Then the reduced problem has been converted to unconstrained optimization problem with interval objective by Big-M penalty technique. The resulting problem has been solved by advanced real coded genetic algorithm with interval fitness, tournament selection, intermediate crossover and one-neighbourhood mutation. Findings: – A new optimization technique has been developed in stochastic domain and the concept of interval valued parameters has been integrated with the stochastic setup so as to increase the applicability of the resultant solution to the interval valued nonlinear optimization problems. Practical implications: – The concept of probability distribution with interval valued parameters has been introduced. This concept will motivate the researchers to carry out the research in this new direction. Originality/value: – The application of genetic algorithm is extended to solve the reliability optimization problem in stochastic and interval domain.